Isolation, identification, and quantification of Prevotella intermedia and Prevotella nigrescens in subgingival plaque samples of periodontally healthy and chronic periodontitis patients through chromogenic in situ hybridization - Vijayalakshmi Sharadindu Kotrashetti; Kishore Gajanan Bhat; Vijay Mahadev Kumbar; Sachita Shrikant Naik (Journal of Indian Society of Periodontology)
Background: The genus Prevotella comprising over 50 identified species is a normal commensal of the oral cavity. The commonly studied species are Prevotella intermedia (PI) and Prevotella nigrescens (PN). The molecular technique, used for isolating and identifying these species, requires specialized equipment, making them not feasible in a standard laboratory. Chromogenic in situ hybridization (CISH) can be performed in routine laboratory and is economical and less time-consuming. Hence, the aim of this study was to isolate, identify, and quantify PI and PN from subgingival plaque samples of chronic periodontitis (CP) and periodontally healthy individuals through CISH. Materials and Methods: A total of 100 individuals in the age group of 20–70 years (50 CP and 50 healthy individuals) were considered. Detailed demographic data were obtained from both the groups. Subgingival plaque was collected from the individuals and transferred to reduced transport media and sent to the laboratory for CISH staining. The samples were fixed in 4% paraformaldehyde and then smeared on gelatin-coated slides. The slides were stained using a specific oligonucleotide probe for PI and PN and then subjected to streptavidin-biotinylated horseradish peroxidase complex. The slides were analyzed for bacilli under a light microscope at ×100 magnification for identification and quantification. Results: The number of positive cases for PI was higher in CP (54%) compared to healthy (46%), whereas in PN, the number of positive cases was higher in healthy (66%) compared to CP (54%). When grades of periodontitis were considered, a number of positive cases were higher in percentage with an increase in grade of periodontitis. Quantification of the bacilli showed a mean score of 23 and 33 for PI and PN, respectively, in the healthy group, and a score of 27 for both PI and PN in the CP group. Conclusion: PI appears to have a role in CP when compared to PN based on the quantification of the bacilli in healthy subjects, which showed a decreased PI score and increased PN score. CISH appears to be one of the promising diagnostic tools for the identification of oral bacteria, as it is simple, less time-consuming, accurate, and specific for the identification of microbes.